Review article: Roles of activities of daily living and frailty assessments for residents of residential aged care services in emergency department transfers: A scoping review. (20th August 2022) - Smyth, James; Umapathysivam, Kandiah; Hendrix, Ivanka; Grantham, Hugh; Arendts, Glenn; Visvanathan, Renuka
Abstract: Residents from residential aged care services (RACS) (i.e. nursing homes) many of whom are frail or disabled, are frequently transferred to ED for treatment of acute episodes of illness or injury. This review scoped the research related to the ways in which frailty or activities of daily living (ADL) measures are used for clinical purposes, either prior to the transfer of patients to ED or in ED themselves. A search for original studies up to June 2021 that included participants aged 65 years or over was conducted across four databases. Abstracts were first reviewed, leading to full text screening and article selection. Thirty‐four studies were included in the scoping review. Most of the ADL and frailty assessments were conducted in residential aged care settings. In seven studies, ADL or frailty assessments in the aged care setting contributed to reduced transfer rates to ED. No results were found that associated the assessment of ADL or frailty with decisions related to treatment in the ED. A single ED study involved specialist emergency nursing in an ED as an intervention which included frailty assessment and led to decreased hospitalisation. This scoping review confirms an opportunity for further research into the ways frailty and ADL assessments are used for decision making in relation to the transfer of frail older people to ED, including how these assessments influence their treatment. Abstract : This scoping review was set to look at how assessments of frailty and activities of daily influence clinical decision making related to relatively frequent transfers of residential aged care services (RACS) residents to the ED. From 34 studies included in the review, the main findings were that that the assessments are done less frequently and seldom applied or shown to influence clinical decision making in the ED compared to the RACS. This confirms an opportunity for further research on the role of the assessments in the ED.